Financial Instability: A Recession Simulation on the U.S. Corporate Structure - Dorene Isenberg (Levy Economics Institute of Bard College, 1989)
This study is a continuation of the empirical research on the impacts of debt; it argues that debt-usage is not neutral and that the currency of its cost is bankruptcy. A financially fragile economy is feared because of its potential harm. In the public sector the large and lingering deficit is not a problem in and of itself. It is only when future scenarios of budget item trade-offs or recession-fighting fiscal policy options are conjured up that the problem emerges. The same is true for the corporate debt. As long as the debt is incurred in an expanding economy, there is no economic problem. It is only when a contraction ensues that the problem emerges. The problem is encapsulated in bankruptcy and the costs that accompany it. Some of these costs are private and can be born by the managers and owners. However, in a recession this burden grows and spreads beyond the private; the costs become socialized. While previous researchers have indicated the extent of consumer and producer indebtedness, this study uses discriminant analysis to simulate the impact of a recession on the manufacturing sector so that a measure of our current financial vulnerability is produced. In the first section background material on the current financial structure of the United States is reviewed. The second section delineates the social costs of bankruptcy. The construction and characteristics of the discriminant function are specified in the third section. The fourth section details the simulation and its results.
Keywords: 330